Neural correlates of episodic memory in adults with Down syndrome and Alzheimer’s disease - Bessy Benejam; Mateus Rozalem Aranha; Laura Videla; Concepción Padilla; Silvia Valldeneu; Susana Fernández; Miren Altuna; Maria Carmona-Iragui; Isabel Barroeta; Maria Florencia Iulita; Víctor Montal; Jordi Pegueroles; et al. (Alzheimer’s Research & Therapy, 2022)
Abstract Background Adults with Down syndrome are at an ultra-high risk of developing early-onset Alzheimer’s disease. Episodic memory deficits are one of the earliest signs of the disease, but their association with regional brain atrophy in the population with Down syndrome has not been explored. We aimed to investigate the neuroanatomical correlates of episodic memory in adults with Down syndrome and symptomatic Alzheimer’s disease. Methods Single-center, cross-sectional study. A total of 139 adults with Down syndrome (85 asymptomatic and 54 with symptomatic Alzheimer’s disease) were included in the study (mean age 43.6 ± 10.9 years, 46% female). Episodic memory was assessed using the modified Cued Recall Test. Immediate (trial 1 free immediate recall, trial 3 free immediate recall, total free immediate recall score, and total immediate score) and delayed scores (free delayed recall score and total delayed score) were examined. Cortical thickness from magnetic resonance imaging was determined with surface-based morphometry using the FreeSurfer 6.0 software package. The clusters of reduced cortical thickness were compared between symptomatic and asymptomatic participants to create a cortical atrophy map. Then, the correlation between cortical thickness and the modified Cued Recall Test subscores were separately assessed in symptomatic and asymptomatic subjects, controlling for age, sex, and severity of intellectual disability. Results Compared with asymptomatic participants, those with symptomatic Alzheimer’s disease showed a pattern of cortical atrophy in posterior parieto-temporo-occipital cortices. In symptomatic subjects, trial 1 immediate free recall significantly correlated with cortical atrophy in lateral prefrontal regions. Trial 3 free immediate recall and total free immediate recall were associated with the most widespread cortical atrophy. Total immediate score was related to posterior cortical atrophy, including lateral parietal and temporal cortex, posterior cingulate cortex, precuneus, and medial temporal lobe areas. Delayed memory scores were associated with cortical atrophy in temporoparietal and medial temporal lobe regions. No significant relationships were observed between episodic memory measures and cortical atrophy in asymptomatic subjects. Conclusions Different episodic memory measures were associated with cortical atrophy in specific brain regions in adults with Down syndrome and Alzheimer’s disease. These results overlap with those described in sporadic Alzheimer’s disease and further support the similarities between Down syndrome-associated Alzheimer’s disease and that in the general population.